(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article deals with the issue of realization of the interests of youth in Uzbekistan. It also focuses on the fact that the policy of caring for young people living in the country is a general guiding principle of society aimed at ensuring the priority of human interests.